Health-related quality of life of the elderly after natural disasters: a scoping review - Pujiatun Pujiatun; Anindya K Zahra; Detty Siti Nurdiati (Universitas Gadjah Mada, 2023)
Every nation on earth is experiencing an increase in the number and proportion of elderly people. This vulnerable population may experience a decline in health-related quality of life (HRQOL) following a natural disaster. This scoping review aimed to have a better understanding on the elderly’s HRQOL following natural disasters, its influencing factors, and the state of the research on this topic. A literature search was conducted using four databases (PubMed/MEDLINE, Cochrane Library, Science Direct, and ProQuest) for the last 10 years (2013–2022). The summary of the selected relevant articles and analysis data were used to present the findings. There were seven articles included in our review. One article was about floodsand the rest was about earthquake.Two out of the six earthquake articles involved tsunamis. All of the studies were conducted during the recovery phase and revealed that the elderly had poor HRQOL after natural disasters. Several aspects, including demographics, physical, psychological, social, and environmental factors, were identified as having impacts on the elderly‘s HRQOL following a disaster. The relocation had a significant negative impact on the mental health of the elderly, with a mean difference of -3.69 (-5.60, -1.77). In conclusion, the HRQOL of the elderly after a natural disaster is low and affected by several factors. To improve it, a stronger research agenda and disaster management programs that take these factors into account are required.